Active Peptic Ulcer Disease in Patients with Hepatitis C Virus-Related Cirrhosis: The Role of Helicobacter pylori Infection and Portal Hypertensive Gastropathy - Maria Dore; Daniela Mura; Stefania Deledda; Emmanouil Maragkoudakis; Antonella Pironti; Giuseppe Realdi (Canadian Journal of Gastroenterology)
BACKGROUND & AIM: The relationship between Helicobacter pylori infection and peptic ulcer disease in cirrhosis remains controversial. The purpose of the present study was to investigate the role of H pylori infection and portal hypertension gastropathy in the prevalence of active peptic ulcer among dyspeptic patients with compensated hepatitis C virus (HCV)-related cirrhosis.